2015
DOI: 10.1007/s00253-015-7217-6
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous denitrification and phosphorus removal by Agrobacterium sp. LAD9 under varying oxygen concentration

Abstract: Although efficient aerobic denitrification has received increasing attention, few studies have been made on simultaneous denitrification and phosphorus removal (SDPR) under aerobic condition. In this study, SDPR by an efficient aerobic denitrifier, Agrobacterium sp. LAD9, was firstly demonstrated. High nitrate and phosphorus removal rates of 7.50 and 1.02 mg L(-1) h(-1) were achieved in wide range of O2 concentration from 5.92 to 20.02 mg L(-1). The N2O production would be inhibited as O2 concentration exceede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 37 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…The concentration of dissolved N 2 O was determined using the headspace method with a gas chromatograph (GC, Thermo Scientific Fisher Trace 1310, USA). , The GC was equipped with an electron capture detector (ECD) and a 5 Å molecular sieve column (30 m × 0.32 mm × 30 μm). The carrier gas was N 2 at a flow rate of 5 mL min –1 .…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of dissolved N 2 O was determined using the headspace method with a gas chromatograph (GC, Thermo Scientific Fisher Trace 1310, USA). , The GC was equipped with an electron capture detector (ECD) and a 5 Å molecular sieve column (30 m × 0.32 mm × 30 μm). The carrier gas was N 2 at a flow rate of 5 mL min –1 .…”
Section: Methodsmentioning
confidence: 99%
“…NO 3 → NO 2 → NO → N 2 O → N 2 ) but this would require strict anaerobic conditions, presenting significant compatibility issues with waste gas streams that contain high levels of oxygen. 70 Nevertheless, some have reported the existence of aerobic denitrifying bacteria such as Pseudomonas aeruginosa that may be useful for NOx removal from waste gases that contain oxygen. 71 As engineering an optimal MES microbiome may be a complex task, a more elegant approach to improve MES compatibility with waste gas blends may be to develop new porous 3D electrode nanomaterials.…”
Section: Bio-electrocatalytic Co 2 Conversion Nanomaterialsmentioning
confidence: 99%
“…In addition, the use of phosphorus in the production of EPS of Agrobacterium strains was evaluated, and it was found that phosphorus limitation increases the production of substances that help in the formation of biofilms and granules by species of this bacterial genus (Huang et al 2012). The use of phosphorus in the EPS production of Agrobacterium strains was evaluated by Ma et al (2016). The limitation of phosphorus increases the production of substances that contribute to the formation of biofilms and granules by species of this bacterial genus.…”
Section: Humic Acid Quantificationmentioning
confidence: 99%